Pendugaan Parameter Genetik dan Korelasi Beberapa Karakter Vegetatif Jambu Mete Populasi Sumba Barat Daya - Saefudin Saefudin; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Estimation of genetic parameter of cashew are important as the basis information for the next breeding programm. The research was conducted at Cikampek Experiment Station at altitude about 50 m above sea level, Laterite type of soil and C type of climate, beginning from January 2009 until January 2011. The objectives of this research are to: (1) estimate the genetic parameters which include the coefficient of genetic variability, heritability, and genetic advances, and (2) analyze the genotypic and phenotypic correlations between vegetative characters of cashew from Sumba Barat Daya populations (SBD). Randomized Complete Block Design with eight treatments of accession numbers of cashew with three replications was used in this study. Variables measured were the components of vegetative growth i.e. : height of plant (TT), stem diameter (DB), number of branches (JC), canopy width of U-S (LTUS), canopy width of B-T (LTBT), height of the first branching (TPP), length of leaves (PD), width of leaves (LD), and ratio of width and length of leaves (RLPD). Results showed that: (1) in general the genetic variability of vegetative characters of cashew in SBD populations were narrow, except number of branch and height of first branch characters. The improvement of number of branch characters has a high probability and success by breeding programm; and (2) genetically number of branch characters has a positive correlation with height of plant, canopy width of U-S, and canopy width of B-T, but a negative correlation with height of first branch characters.